Visual Media in Foreign Language Class Room - Brigita Kosevski Puljić; Andreja Retelj (Vestnik za Tuje Jezike, 2013)
In this article authors discuss the role of visual media in the context of foreign language teaching and learning in the era of modern technology. They describe the study they carried out with teachers of German language in order to see how they use the interactive whiteboard to enhance the language development through the visual media presented on this equipment. Their findings indicate that most of the teachers use interactive whiteboard as a tool to support teaching and not as a tool that supports the process of learning. The authors suggest more learner-centered and task-based approaches to teaching in order to achieve easier and meaningful learning instead of using technology only to make the lessons more attractive and up to date.